The design of a labyrinth seal to replace the centrifugal compressor of a turbojet, for transforming the turbojet into a turboexpander - Sirbu, Theodor Mihnea; Nan, Diana Andreea; Profir, Calin; Mandreanu, Ioana Cristina; Amariutei, Mara; Suciu, Cosmin Petru; Hank, Alexandru; Navligu, Bogdan; Stanciuc, Ramona-Manuela; Vlăducă, Iulian (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
In the last 10 years, the development of microturboreactors has experienced an exponential evolution. They have recently gained interest due to the significantly higher power output, which is primarily achieved by expanding the speed ranges of the key components, namely the compressor and the turbine. Also, the development of bearings with ceramic balls (also known as hybrid bearings) at high speeds of 80,000 rpm in the case of the present work, brings a challenge regarding the design of the main components (compressor + turbine), which must withstand very high centrifugal force demands that increase with the diameter of the component, especially for the turbine that faces additional thermal stress, respectively reaching a creep limit. From a technical standpoint, at relatively low power consumption, the challenges have been addressed for turbojets with a modest thrust of 40 daN (90 lbf), making such turbojets available at relatively low prices [1]. In the present work it is proposed to modify a 40 daN (90 lbf) turbojet and transform it into an axial turboexpander [2] capable of theoretically gearing an electric generator of 132/160 kVA (177/215 HP), by means of a gear reducer taking into account the losses related to the gear reducer and the electric generator. The proposed transformation has commercial values, such axial turboexpanders are able to work in electricity generation mode having the availability of a relatively low source of compressed air of maximum 10 bar (150 PSI).